Different Effects of Two Protocols for Pre-Procedural Analgosedation on Vital Signs in Neonates during and after Endotracheal Intubation - Zemlin, Michael; Buxmann, Horst; Felgentreff, Sabine; Wittekindt, Boris; Goedicke-Fritz, Sybelle; Rogosch, Tobias; Göbert, Pia; Meyer, Sascha; Sauer, Harald; Greene, Brandon H; Schloesser, Rolf L.; Maier, Rolf Felix (Klinische Pädiatrie, 2021)
Background Analgosedation is often used for endotracheal intubation in neonates, but no consensus exists on the optimal pre-procedural medication.Aims To compare the time to intubation and vital signs during and after intubation in 2 NICUs using different premedication protocols.Methods Prospective observational study in 2 tertiary NICUs, comparing fentanyl and optional vecuronium for elective neonatal endotracheal intubation (NICU-1) with atropine, morphine, midazolam and optional pancuronium (NICU-2). Primary endpoints were: time to intubate and number of intubation attempts; secondary endpoints were: deviations of heart rate, oxygen saturation and blood pressure from baseline until 20 min post intubation.Results 45 and 30 intubations were analyzed in NICU-1 and NICU-2. Time to intubation was longer in NICU-1 (7 min) than in NICU-2 (4 min; p=0.029), but the mean number of intubation attempts did not differ significantly. Bradycardias (34 vs. 1, p<0.001) and hypoxemias (136 vs. 48, p<0.001) were more frequent in NICU-1, and tachycardias (59 vs. 72, p<0.001) more frequent in NICU-2. Mean arterial blood pressure (MAP) increased in NICU-1 (+6.18 mmHg) and decreased in NICU-2 (−5.83 mmHg), whereas mean heart rates (HR) decreased in NICU-1 (−19.29 bpm) and increased in NICU-2 (+15.93 bpm). MAP and HR returned to baseline 6–10 min after intubation in NICU-1 and after 11–15 min and 16–20 min in NICU-2, respectively.Conclusions The two protocols yielded significant differences in the time to intubation and in the extent and duration of physiologic changes during and post-intubation. Short acting drugs should be preferred and vital signs should be closely monitored at least 20 min post intubation. More studies are required to identify analgosedation protocols that minimize potentially harmful events during endotracheal intubation.
Keywords: Neonate; Premedication; Endotracheal intubation; Vital signs; Preterm infants; Adverse effects